How victim credibility and cooperation influence investigative decision-making: examining DOJ's gender bias principles for investigating domestic and sexual violence. Issue 4 (29th April 2021) - Growette Bostaph, Lisa; King, Laura L.; Brady, Patrick Q.
Abstract : Purpose: The purpose of this exploratory study is to examine if and how victim credibility affects investigative decision-making and case outcomes in domestic violence and sexual assault reports through the use of the US Department of Justice's Gender Bias Principles (GBPs). Design/methodology/approach: The authors conducted a content analysis of 370 DVSA police reports from one agency in the western US. Multivariate regression models were estimated to examine the relationships among victim credibility and investigative activities, victim cooperation and case clearance. Findings: Victim credibility significantly predicts specific investigative actions and case clearance, but not victim cooperation. Multiple aspects of DVSA investigations significantly impact victim cooperation as well as case clearance, regardless of victim credibility issues. The GBPs are an effective framework for disaggregating investigative activities and identifying specific areas for improvement in policing response to DVSA. Research limitations/implications: Further study is needed to determine the temporal ordering of officer assessment of victim credibility and investigative activities, the stability of such assessments during investigations, and if credibility problems noted in police reports are valid indicators of myth acceptance among officers or represent a downstream orientation of information requested by prosecutors. Victim service referral as a part of policing response is vastly under-researched given referral's strong effects on victim cooperation and case clearance. Crime-specific differences exist in many cases, yet not in others, suggesting separate and combined DVSA analyses are warranted. Practical implications: A more complex analysis of investigative actions offers a targeted approach to officer training and administrative rule-making that may be more efficient and effective than current generalized approaches. Originality/value: The study is the first to empirically test the utility of the GBP framework, as well as individual aspects of DVSA investigations, and from a gender-based crime rather than crime-specific approach.